The Global Impact of COVID-19 on the Care of People With Endometriosis - Demetriou, Lysia; Cox, Emma; Lunde, Claire E.; Becker, Christian M.; Invitti, Adriana L.; Martínez-Burgo, Beatriz; Kvaskoff, Marina; Garbutt, Kurtis; Evans, Emma; Fox, Elaine; Zondervan, Krina T.; Vincent, Katy (Frontiers in Global Women's Health, 2021)
Endometriosis is a chronic condition affecting ~10% of women globally. Little is known about the impact of the coronavirus disease 2019 (COVID-19) pandemic on their care. This brief report is aimed to explore the impact of COVID-19 on the care of people with endometriosis around the world, their priorities in relation to their clinical care during and coming out of the pandemic, and whether they believed that endometriosis makes them more vulnerable to COVID-19. An internet-based survey collected data in five languages between May 11, 2020, and June 8, 2020. Only participants with a surgical or radiological diagnosis of endometriosis aged 18 years or over were included. A total of 6,729 eligible respondents completed the survey with 80.7% [95% CI (79.7, 81.6)] reporting a negative impact on their care. This included difficulties obtaining medication (20.3%), cancelled/postponed gynaecology appointments (50.0%), and cancelled/postponed procedures (37.2%). More than half worried that their endometrioses make them more vulnerable to COVID-19 [54.2%; 95% CI (53.0, 55.4)]. The top three priorities were remarkably consistent around the world: contact with gynaecologists, knowing when procedures would be performed, and support with mental health (20.3% prioritising this aspect during the pandemic and 13.0% as restrictions begin to ease). This study shows the substantial impact the COVID-19 pandemic has had on people with endometriosis and describes how they would like care prioritised moving forwards. The findings regarding significant support needs for mental health add further weight to the growing recognition of attending to such issues as part of good patient-centred care.